AN ANALYSIS OF FIGURATIVE LANGUAGE IN MICHAEL JACKSON SONG LYRICS - Herman Herman; Dewi Sri Lumbantobing; Bloner Sinurat (English Education Study Program Faculty of Teacher Training and Education, 2021)
This research aims to find out the figurative language in Michael Jackson song lyrics. Therefore, the researchers formulated a question as the problem. As follows: (1) what are the kinds of figurative language in Michael Jackson’s song lyrics? (2) What is the dominant type of figurative language in Michael Jackson’s song lyrics? This research used Perrine theories to analysis kinds of figurative language in Michael Jackson song lyrics. There are 12 types of figurative language according to Perrine they are: simile, metaphor, personification, apostrophe, synecdoche, metonymy, symbol, allegory, paradox, hyperbole/overstatement, understatement, and irony. The researchers used qualitative design because data are collected by using document in form of word and a procedure of systematic analysis of context text (words, phrase, sentences, document, etc), analysis content by qualitative enable researchers to understand the text by grouping words that have same meaning into categories. The researchers used ten song from the website Genius.com as an instrument to find the data to be analyzed based types of figurative language. The researchers finding showed that are 6 types of figurative language that found in Michael Jackson’s Songs namely: personification, apostrophe, metaphor, hyperbole, simile and symbol. While, there are 6 types of figurative language weren’t found in Michael Jackson’s Songs namely: synecdoche, metonymy, allegory, paradox, understatement, and irony. After analyzing all the data the researchers found the types of figurative language are dominantly used in Michael Jackson’s songs are hyperbole consists of 11 sentences (30%).